2016
DOI: 10.1007/s00477-016-1261-3
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation trend analysis using discrete wavelet transform at the Langat River Basin, Selangor, Malaysia

Abstract: The main purpose of this study was to determine the most dominant periodic components that affect the annual and seasonal precipitation trends in each homogenous rainfall region in the Langat River Basin, Malaysia for the period 1982-2011. Performing this research could be essential because in the previous studies on detection of trend in Malaysia, the details of variations of different time scales and the periodic responsible for the observed trends were not investigated. Using discrete wavelet transform (DWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Previous studies indicated that the interpolation methods should account for external factors, such as altitude and land use patterns [42]. However, compared with other interpolation methods, the IDW produced slightly better predictions of ET 0 [29,43]. Future studies should consider how different interpolation methods impact the spatial variations of ET 0 at different time scales.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies indicated that the interpolation methods should account for external factors, such as altitude and land use patterns [42]. However, compared with other interpolation methods, the IDW produced slightly better predictions of ET 0 [29,43]. Future studies should consider how different interpolation methods impact the spatial variations of ET 0 at different time scales.…”
Section: Discussionmentioning
confidence: 93%
“…The change points were detected based on the sequential MK test, which has been largely employed for the detection of change points in different climatic and hydrological data series [28][29][30]. Detailed information related to the sequential MK test can be found in studies published by Palizdan et al [29] and Liang et al [30]. In addition, Sen's slope estimator was used to measure the magnitude of the trend [31].…”
Section: Trend Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Although, several studies are available focusing on application of DWT in trend analysis (Partal and Küçük, 2006;Adamowski et al, 2009;Nalley et al, 2012;Nalley et al, 2013;Adarsh and Janga Reddy, 2015;Araghi et al, 2015;Adarsh et al, 2016;Joshi et al, 2016;Palizdan et al, 2017), there exists lack of a micro-level study focusing on regional precipitation patterns in India. Considering this gap, the present study is intended to analyse trends and identify dominant periodic component in various rainfall time series over various districts of Chhattisgarh state (a semi-arid region) in India using DWT in conjunction with MK and SQMK test.…”
Section: Introductionmentioning
confidence: 99%